(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the diagnostic performance of the iPonatic mPOCT system for HPV detection compared with multiplex real-time PCR and to analyze the impact of disease prevalence on predictive values. Subject and methods: A cross-sectional diagnostic study was conducted on 294 cervical samples collected from women attending gynecological clinics. All samples were tested using both the iPonatic mPOCT system and multiplex real-time PCR (reference method). Diagnostic performance indicators, including sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, positive predictive value, negative predictive value, and overall accuracy, were calculated with 95% confidence intervals. Positive predictive value and negative predictive value were further modeled under three assumed prevalence levels: 13.6%, 16.5%, and 18.82%. Results: The iPonatic system demonstrated a sensitivity of 88.6% (95% CI: 75.4-96.2) and a specificity of 99.2% (95% CI: 97.1-99.9) based on the analysis of 294 samples. The positive likelihood ratio was 110.8 (95% CI: 27.8-442.4), and the negative likelihood ratio was 0.11 (95% CI: 0.05-0.26). When disease prevalence increased from 13.6% to 18.82%, positive predictive value increased from 94.6% to 96.3%, while negative predictive value slightly decreased from 98.2% to 97.4%. Overall diagnostic accuracy ranged from 97.2% to 97.8%. Conclusions: The iPonatic mPOCT system demonstrated very high specificity and good sensitivity compared with multiplex real-time PCR for HPV detection. The predictive performance of the test varied according to disease prevalence. iPonatic may represent a practical option for HPV testing in clinical settings, particularly in resource-limited environments or populations with moderate to high HPV prevalence